EFEKTIVITAS PENERAPAN EDUKASI PRAKTIK MENYUNTIK YANG AMAN TERHADAP PERUBAHAN PERILAKU PERAWAT DALAM MENYUNTIK DI RUANG HARDJA IIA RS BHAYANGKARA TK. I RADEN SAID SUKANTO - Farras Jihan Afifah, (2022)
Safe injection practices are actions that do not harm patients and must avoid risks to healthcare workers. Unsafe injection practices are risky for needle-stick incidents. Pathogens that can be transmitted from needle-sticks are Hepatitis B, Hepatitis C and HIV. Based on a survey by WHO, the incidence of needle-sticks in healthcare workers was 3 million incidents. In Hardja IIA room at Bhayangkara Hospital Tk. I Raden Said Sukanto, 85.7% of nurses are still recapping. This writing aims to measure the effectiveness of safe injection practices by nurses in Hardja IIA at Bhayangkara Hospital Tk. I Raden Said Sukanto. The results showed there was a change in the preparation of injections on table or tray from 71.4% to 100%, washing hands before preparing injections from 57.1% to 100%, using handscoon from 42.9% to 71.4%, using barrier when breaking ampoules from 28.6% to 85.7%, applying 7 correct in drug administration from 42.9% to 85.7%, cleaning rubber at the top of vial with an alcohol swab from 71.4% to 100%, from 85.7% of nurses who recapped to 100% of nurses who didn't recap, dispose sharps waste immediately from 71.4% to 100%. Nurses are expected to apply and increase awareness in safe injection practices.